Determination of employee performance: Analysis of training, work motivation, transformational leadership and organizational culture - Rachman, Subehana; B, Joe Alend Seniza.; Susanto, Primadi Candra; Mustika, Ika (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine the key determinants of employee performance in the Indonesian maritime sector, particularly among ship crew members. The factors analyzed include training, work motivation, transformational leadership, and organizational culture, with the goal of understanding how these variables contribute to enhancing crew effectiveness, discipline, and productivity. Research Methodology: A descriptive qualitative approach using the SALSA (Search, Appraisal, Synthesis, and Analysis) framework was employed. A total of 30 peer-reviewed articles from academic databases published within the last eight years were systematically reviewed. The study used theoretical triangulation by applying established models such as Human Capital Theory, Maslow’s Hierarchy of Needs, Bass’s Transformational Leadership, and Hofstede’s Organizational Culture Framework. Results: The findings reveal that training improves job competence, work quality, and accountability; motivation enhances commitment and timeliness; transformational leadership fosters trust, innovation, and responsibility; and organizational culture strengthens discipline, teamwork, and loyalty. Each variable positively influences employee performance in the maritime context. Conclusions: Investments in human resource factors particularly training, motivation, leadership, and organizational culture are crucial for enhancing the performance of maritime personnel. These factors serve as strategic levers to improve safety, operational efficiency, and service quality in the shipping industry. Limitations: The study is limited to secondary data from literature published in English and Bahasa Indonesia, lacks empirical field validation, and does not explore the interaction effects among the variables. Contribution: This study contributes conceptually by offering a synthesized framework linking human resource variables to maritime performance, thereby guiding future empirical research and managerial interventions in crew development and organizational transformation.